The social setting of the ministry as reflected in the writings of Hermas, Clement and Ignatius - Maier, H (1987)
This thesis contributes to a growing body of literature concerned with the social setting of early Christianity. It focuses on three first and early second century documents (the Shepherd of Hernias, 1 Clement, and the Ignatian epistles) and reconstructs from them the social setting of the ministry in Rome, Corinth, and Asia Minor. Relatively well-to-do patrons who invited the church to meet in their homes were the primary leaders of these communities. No attempt is made to generalize from these centres to other places. The Shepherd of Hermas is interpreted, not as a theological treatise which attempts to solve theological problems of post-baptismal sin, but rather as expressing Hermas' social concern (one typical of sects) to protect the purity of his group. Challenges presented by prosperous householders (who were bishops) resulted in Hermas' attempts to strengthen group boundaries, thereby insulating the church from worldly influences. 1 Clement is treated not as evidence of the advent of mstitutionalizoiion in the early church, but rather as the attempt to end division rooted in a house-church structure. Following Berger and LucKmann's model of institutionalization and legitimation, it is seen as an attempt to legitimate institutions of leadership which had formed through the interaction of house-church hosts with Paul. By showing how beliefs committed members to support certain leaders, Clement legitimated their authority. Rather than the expression of mystical Je^ire tor unity with God, Ignatius' letters are interpreted (using Weber's charismatic type) as the efforts of an 3 ut ho r-ity using his extraordinary position to protect communities from divisive house-church meetings. Protection from false teaching was initiated by reinforcing the position of bishops (the hosts of the common euchanstic assembly).